Implementation of Ministry of Transportation Regulation Number 45 of 2020 concerning Certain Vehicles with Electric Motors: A Case Study of Underage Riders in Medan City from the Perspective of Siyasah Dusturiyah - Mohd. Tauhid Adsri; Irwansyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study examines the implementation of the Ministry of Transportation Regulation Number 45 of 2020 concerning certain vehicles powered by electric motors, focusing on the phenomenon of underage drivers operating these vehicles on public roads in Medan City. The main objective of this research is to evaluate the effectiveness of the regulation and identify the obstacles faced in its implementation. Using a qualitative approach with a case study design, data were collected through interviews, field observations, and document analysis. The findings reveal that although the regulation provides a clear legal framework, its enforcement remains ineffective, particularly in preventing underage drivers from using electric vehicles on public roads. The contributing factors to this ineffectiveness include low legal awareness among parents and children, weak supervision, and limited public socialization regarding the regulation. From the perspective of fiqh siyasah (Islamic political jurisprudence), government policies should prioritize the public interest and the protection of life (hifz al-nafs). This study recommends stricter law enforcement and more intensive public education to improve legal awareness and ensure the safety of children.